Preservation of The Tortor Mangalo alo Tondong Tradition in Simalungun Batak Weddings in Siopat Suhu Village, Pematang Siantar City - Valda Lia Purba; Supsiloani Supsiloani (STABN RADEN WIJAYA WONOGIRI, 2025)
This study aims to analyze the importance of the Mangalo-alo Tondong Tortor Tradition carried out in the Simalungun Batak Wedding in Siopat Suhu Village, Pematangsiantar City, Explaining the efforts made by the Simalungun community to preserve traditions and knowing how the Simalungun Young Generation views the importance of the Tradition in Simalungun Weddings in Siopat Suhu Village, Pematangsiantar City. The method used in this study is a qualitative method with a descriptive approach. This research was conducted in Siopat Suhu Village, Pematangsiantar City. The data collection techniques are by data reduction, data presentation and drawing conclusions. The results of this study indicate that the Mangalo-alo Tondong Tradition is still carried out and is still preserved by the Simalungun community, both traditional leaders, Simalungun parents, and also the Simalungun Young Generation. Because the role of Tondong is very important in marriage, this tradition is carried out as a form of respect. If in marriage gets a blessing from the Bone, it will be happy together forever according to the Batak people's view. And also to strengthen the relationship between two large families that they all need each other. In the context of Bronislaw Malinowski's functionalist theory, traditions and rituals must serve a function in social life to maintain and pass down to younger generations. Through these traditions, we can see that something with a role and function will be respected and maintained so that it continues to exist.